2020
DOI: 10.1101/2020.06.26.20135715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic epidemiology of SARS-CoV-2 in Colombia

Abstract: Coronavirus disease 2019 (COVID-19) was first diagnosed in Colombia from a traveler arriving from Italy on February 26, 2020. To date, available data on the origins and number or introductions of SARS-CoV-2 into the country are limited. Here, we sequenced SARS-CoV-2 from 43 clinical samples and-together with another 73 genomes sequences available from the country-we investigated the emergence and the routes of importation of COVID-19 into Colombia using epidemiological, historical air travel and phylogenetic o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
2
13
0
2
Order By: Relevance
“…These observations are in line with the known epidemiology of the pandemic (5). Furthermore, the analysis of genomic data has shown that Peruvian isolates were widely distributed across the phylogenetic tree suggesting multiple, independent introductions, designed as nodes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) with over 70% of statistical support from ML ( Figure 1A and Table 1). Similar to these introductions it has been reported in other countries such as Brazil (6), Colombia (7) and the USA (8).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…These observations are in line with the known epidemiology of the pandemic (5). Furthermore, the analysis of genomic data has shown that Peruvian isolates were widely distributed across the phylogenetic tree suggesting multiple, independent introductions, designed as nodes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) with over 70% of statistical support from ML ( Figure 1A and Table 1). Similar to these introductions it has been reported in other countries such as Brazil (6), Colombia (7) and the USA (8).…”
Section: Resultssupporting
confidence: 74%
“…In addition, most introductions into South America countries (e.g. Colombia or Brazil) included European B lineages isolates (6,7,12). However, any other factors might be involved including uneven sampling, chance and epidemiology reasons (13).…”
Section: Resultsmentioning
confidence: 99%
“…We observed branch support values less than 80%, similar to other studies, 10‐12 which may be explained because bootstrap needs diverged sequences 13 , and SARS‐COV‐2 represents a novel virus in recent process of evolution. Therefore, we considered to add branch points of mutations detected using phylodynamics.…”
Section: Figuresupporting
confidence: 86%
“…The combination of several mutations and phylogenetic associations provides information that helps to determine the origin of the viral genotypes, and so theoretically, if we know the origin of the genotypes, both local and imported cases can be detected allowing us to track the dynamics of viral spread at a local and global level. Thanks to molecular epidemiology, it has been possible to detect the emergence, introduction and transmission of new variants of the virus in different regions during this current pandemic [ 10 , 31 , 32 , 33 , 34 ]. This information is vital for developing public health interventions and policy to control viral spread.…”
Section: Discussionmentioning
confidence: 99%